Scale Economies and Cities - Gill, Indermit S. (World Bank, 2012)
This paper summarizes the policy-relevant insights of a generation of research on scale economies. Scale economies in production are of three types: internal economies associated with large plants, localization economies that come from sharing of inputs and infrastructure and from greater competition among firms, and urbanization economies that are generated through diversity and knowledge spillovers. The benefits (and costs) of localization and urbanization are together called “external (dis) economies” because they arise due to factors outside any single household, farm or firm. The empirical literature yields some stylized facts. Internal scale economies are low in light industries and high in heavy industries. External scale economies are amplified by economic density and dissipate with distance from places where economic activity is concentrated. Scale economies are most visibly manifest in towns and cities. To simplify somewhat, towns allow firms and farms to exploit internal scale economies, medium-sized cities help firms in an industry exploit localization economies, and large cities and metropolises provide urbanization economies to those who locate within or nearby. Scale economies have implications for policy makers. The first is that because urban settlements rise and thrive because market agents demand their services, they should be seen as creatures of the market, not creations of the state. The second is that because settlements of different sizes provide differing services, towns, cities, and metropolises are more often complements for one another, not substitutes. Third, as a corollary, policymakers should aim to improve the functioning of urban settlements, and not become preoccupied with their size.